1965
DOI: 10.1111/j.1423-0410.1965.tb01390.x
|View full text |Cite
|
Sign up to set email alerts
|

An Agglutinin Associated with the P and the ABO Blood Group Systems

Abstract: Résumé On décrit les réactions d'un sérum qui agglutine la majorité d'échantillons d'érythrocytes humains. Le donneur de ce sérum est un noir, M. Luke P., qui souffrait de tumeur lymphomateuse; il n'avait jamais été préalablement transfusé. Il y a trois degrés de réactions: la plupart des échantillons sont Luke(1) ou Luke(w); les réactions Luke(‐) sont présentes chez les erythrocytes des personnes de phénotype rare «p» ou «Pk», et, ceci parmi le 2% des caucasiens pris au hasard. Les réactions Luke(w) et Luke(‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

1968
1968
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 4 publications
1
30
1
Order By: Relevance
“…However, the pattern of the score distribution in this study is very similar to that reported by Tippett et al [1], whereas a study based on the monoclonal antibody MC813-70 (anti-SSEA-4) did not quite reach this conclu sion [2). The obviously increased number of weakly LKE-positive donors in group A as compared to group 0 might reflect an interference on the level of synthesis or presentation between the ABO and Luke systems rather than a linkage disequili brium on a genetic basis.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, the pattern of the score distribution in this study is very similar to that reported by Tippett et al [1], whereas a study based on the monoclonal antibody MC813-70 (anti-SSEA-4) did not quite reach this conclu sion [2). The obviously increased number of weakly LKE-positive donors in group A as compared to group 0 might reflect an interference on the level of synthesis or presentation between the ABO and Luke systems rather than a linkage disequili brium on a genetic basis.…”
Section: Discussionsupporting
confidence: 60%
“…The previously described association of LKE and P| [1] was confirmed, and seemed restricted to group A donors. The anti-LKE serum also contained anti-P| reactivity.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Based on MAb MC813-70 staining, SSEA-4 has been identified in undifferentiated human embryonic carcinoma cells and seminomas (30). Agglutination of papain-treated human erythrocytes also occurs with MAb MC813-70, identifying the Luke antigen (38,39), but the molecule on which the Luke antigen is carried on erythrocytes has not been isolated and structurally characterized. Thus, the antibody staining data previously reported by Karr et al suggested, but did not prove, that SGG was expressed in human kidney tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, normal P+, LKEN donors still have low levels of MSGG when examined by sensitive methods [3,4]. Despite the incidence of LKEN in the general population, examples of antiLKE are quite rare, with only six examples mentioned in the literature [1,59]. We had the opportunity to reexamine a historical 'anti LKE' from an untransfused, group A, P2, 32 years old woman in her second pregnancy [5,6].…”
Section: Original Article Open Accessmentioning
confidence: 99%